Does Marijuana Use Contribute to Intimate Partner Aggression? A Brief Review and Directions for Future Research - Testa, Maria (Curr Opin Psychol, 2015)
Marijuana users are more likely to perpetrate intimate partner aggression (IPA) than non-users, yet the mechanism responsible for this association is unknown. Recent studies considering the association between episodes of marijuana use and episodes of IPA have failed to find evidence consistent with an acute effect of marijuana. Research gaps are highlighted and a heuristic model of marijuana’s potential effects on IPA is presented. Research priorities include consideration of mediating mechanisms, moderating variables at the individual and couple level, and examination of acute effects of marijuana using daily report and EMA designs.